The Relationship between Social Capital and Migrant Integration, Ethnic Diversity, and Spatial Sorting - Matthew Roskruge; Jacques Poot (Institute of Labor Economics (IZA), 2024)
In this paper, we present evidence from quantitative research over the last decade on how the social capital of individuals in Aotearoa New Zealand is associated with birthplace and, for migrants, years since migration. We also consider the effects of spatial sorting and ethnic diversity on social capital formation. Aotearoa New Zealand has one of the highest rates of immigration in the OECD and, consequently, one of the highest shares of foreign-born individuals in the population. Additionally, the population is characterized by high ethnic diversity and a large indigenous population, with Māori representing 17 percent of the population. Using several data sources, we measure social capital by focusing on participation and volunteering in a range of community activities, perceptions of safety and inclusion, and voting in elections. Regression modelling shows that, as expected, migrants have little local social capital upon arrival. However, differences between their social capital and that of native-born individuals reduce considerably as the duration of residence in Aotearoa New Zealand increases. When the migrant share in a region is larger than the national average, migrants invest less in bridging social capital. Migrant clustering within a region increases their investment in bonding social capital. Bridging activities are associated with better employment outcomes. Less than one in five respondents in the utilized survey data report discrimination, and for migrants, discrimination declines with years of residence. However, the trend in discrimination has been upward over time and particularly affects non-European migrants and persons identifying with Māori and Pacific Peoples ethnicities. Residential location matters. Greater ethnic diversity is associated with the perception of a less safe neighbourhood, but individuals in ethnically diverse regions experience relatively less discrimination. Additionally, there is more involvement in elections in such regions. In contrast, greater ethnic polarisation in regions is associated with less civic engagement and more discrimination.
Keywords: F22; R11; Z13; 330; social capital; ethnic diversity; bonding; bridging; linking; immigrant integration; spatial sorting